PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING UNTUK MENINGKATKAN KEMAMPUAN EKSPLORASI MAHASISWA - Chairunnisa Amelia; Eko Febri Syahputra (Universitas Quality, 2019)
The aims of the study were to determine the effect of the student facilitator and explaining learning model and to determine the improvement of students' skills in the ability to explore law enforcement material in Indonesia at the Primary School Teacher Education Study Program FKIP UMSU 2018-2019 academic year. The first semester student population of Primary School Teacher Education Study Program FKIP UMSU 2018-2019 amounted to 82 students consisting of 2 classes, namely class A morning, B morning, the sample of study was Random sampling. This study used an experimental method with two-group post-test and only design. The normality test of the experimental class showed sig. 0.031 and the control class showed sig. 0.061. Homogeneity test, for the experimental class was 0.797 and the control class was 0.524. Test the effect / linearity for the experimental class and the control group 0.00, which meant that there was an influence between the experimental model and the control model on student exploration, the influence of an experimental model to the exploration was 63.6%. While the control model was 27.4%.